2013
DOI: 10.1160/th12-07-0532
|View full text |Cite
|
Sign up to set email alerts
|

High on treatment platelet reactivity against aspirin by non-steroidal anti-inflammatory drugs – pharmacological mechanisms and clinical relevance

Abstract: Inhibition of platelet function by aspirin results from irreversible inhibition of platelet cyclooxygenase (COX)-1. While sufficient inhibition is obtained at antiplatelet doses (75-325 mg/day) in most (≥95%) treated patients, the antiplatelet effect of aspirin and subsequent cardiovascular risk reduction is much less in clinical settings and disease-dependent. Several reasons for this "high on treatment platelet reactivity" are known. This paper reviews the evidence for an interaction between aspirin and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 76 publications
0
11
0
2
Order By: Relevance
“… 36 Saxena et al 32 confirmed these findings and showed increasing interference with higher celecoxib concentration. Finally, Hohlfeld et al 38 noted discrepancies between aspirin and NSAIDs with respect to both half-life and binding affinity; they concluded that based on half-life, ASA would be inactivated prior to COX enzyme binding, and the presence of an NSAID with ASA would prevent the access of ASA to platelet receptor sites due to differences in binding affinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Saxena et al 32 confirmed these findings and showed increasing interference with higher celecoxib concentration. Finally, Hohlfeld et al 38 noted discrepancies between aspirin and NSAIDs with respect to both half-life and binding affinity; they concluded that based on half-life, ASA would be inactivated prior to COX enzyme binding, and the presence of an NSAID with ASA would prevent the access of ASA to platelet receptor sites due to differences in binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence supports the theory that the timing of NSAID and aspirin administration appears to influence the degree of interaction. 37 , 38 Gurbel et al 37 recommended administering naproxen at least 2 hours after an aspirin dose to diminish the interaction. Following this recommendation, the dosing schedule was altered for our postoperative arthroplasty patients with EC aspirin scheduled for 0600 and 1800 administration daily.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin and ibuprofen inhibit and modify both COX enzymatic pathways necessary for prostaglandin synthesis, thus inhibiting HCC cellular growth through cell cycle arrest and induction of apoptosis (34). However, when aspirin and ibuprofen are taken concomitantly, ibuprofen interferes with the aspirin binding of platelet COX-1 via competitive inhibition or by inducing conformational changes in the COX-1 enzyme that slows down the rate of acetylation by aspirin (35, 36). Aspirin and ibuprofen may also modulate hepatocarcinogenesis through non-COX pathways, such as mitogen-activated protein kinase and PI3K/Akt pathways (21, 37), or down regulation of pro-inflammatory cytokines (38).…”
Section: Discussionmentioning
confidence: 99%
“…120 This interaction is not seen with some other types of NSAID, namely selective cyclooxygenase 2 (COX2) inhibitors and diclofenac. 121 These findings have led to the recommendation by the FDA that individuals on cardioprophylactic doses of aspirin requiring NSAID treatment carefully time the administration of both these drugs or consider treatment with either an analgesic that does not interfere with the anti-platelet effect of low-dose aspirin or a non-NSAID analgesic. 122 Nevertheless, NSAIDs in general are and can be used safely in large numbers of individuals with OA, providing meaningful clinical benefit.…”
Section: Management Optionsmentioning
confidence: 99%